Structure elucidation and toxicological evaluation of cyclic Polyethersulfone oligomers present in extracts of membrane filters. Issue 9 (4th July 2022) - Menzel, Roberto; Maier, Tanja; Täuscher, Eric; von Mertz, Franziska Spruner; Freiberger, Emma; Golz, Christopher; Fruth, Lothar; Pahl, Ina; Hauk, Armin
Abstract: Polyethersulfone (PES) is a widely used polymer in consumer and technical products. An important application is PES membranes used in the biopharmaceutical industry for sterilizing‐grade filtration and for filtration of food and beverages. For both uses, detailed information about migrating compounds that can be extracted from the polymeric material into a liquid must be gathered. In the pharmaceutical industry, comprehensive extractables studies are required for contact materials, and the data is used in the qualification of the process equipment. PES is generated via polycondensation, which forms cyclic oligomers as a by‐product of the reaction. However, no structural information is available for these cyclic oligomers so far. In this publication, we present the analytical determination of PES cyclic oligomers. Their presence in extracts of PES membrane filters is confirmed. The structure of the PES cyclic trimer is elucidated by X‐ray and NMR investigation, obtained as crystals from the sublimation of the PES raw material. A strategy is shown to assess the toxicity of such cyclic oligomers and to derive a permitted daily exposure (PDE). The data will reduce the levels of unknowns in extractables and leachables screenings and supports the risk assessment of PES sterile filters. Abstract : Crystal structure of the cyclic trimer of polyethersulfone (PES) in front of a scanning electron microscope (SEM) image of a PES membrane.